A fogoly (Perdix perdix) tojás morfológiai vizsgálata - Rafaj Marcell Endre (2017)
In the dissertation I examined the partridge eggs’ morphological changes and the value-measuring features such as lenght, width, weight, the calculated volume and the egg index which is used in the country and internationally as well. The enclosed sample area located in the botanical garden of the University of Sopron where the nest-boxes were placed. In 2016 three couples, while in 2017 twelve couples of partridge were involved in the examination. The members of the laying partridge stock was taken from several sources. All in all I examined 543 eggs, which consisted of the eggs of the breeded partridge stock and also the eggs from Lenes and Kecel. In the course of the examination I made observations in connection with the morphological changes which occured during the laying period.